Behavioral and Neural Correlates of Cognitive Training and Transfer Effects in Stroke Patients - Miotto, Eliane C.; Bazán, Paulo R.; Batista, Alana X.; Conforto, Adriana B.; Figueiredo, Eberval G.; Martin, Maria da Graça M.; Avolio, Isabella B.; Amaro, Edson; Teixeira, Manoel J. (Frontiers in Neurology, 2020)
Stroke lesions are frequently followed by cognitive impairments. Cognitive training is a nonpharmacological intervention that can promote neural compensation mechanisms and strategies to remediate cognitive impairments. The aims of this study were: (1) To investigate the cognitive performance, generalization effects and neural correlates of semantic organization strategy training (SOST) in patients with chronic left frontoparietal stroke and healthy controls (HC); and (2) to compare the behavioral effects and neural correlates of SOST with an active control psychoeducation intervention (PI). In this randomized controlled study, all participants were randomly allocated into two groups, one group received SOST, and the other received PI intervention. Participants underwent two fMRI sessions, one prior and the other, after intervention. In each fMRI session, images were obtained during memory encoding task using a list of semantically related words. We found improved post-intervention memory performance in participants that received SOST (both patients and controls), indicated by number of words recalled, word clustering scores and performance in a generalization task. The fMRI analysis revealed negative correlation between task performance and regions of the default-mode network. These results suggest that cognitive training using semantic organization strategy can improve episodic memory performance and promote potential functional neuroplasticity in patients with ischemic stroke lesions.